Racially diverse participant registries to facilitate the recruitment of African Americans into presymptomatic Alzheimer's disease studies. Issue 8 (16th June 2020) - Cocroft, Shelytia; Welsh‐Bohmer, Kathleen A.; Plassman, Brenda L.; Chanti‐Ketterl, Marianne; Edmonds, Henry; Gwyther, Lisa; McCart, Michelle; MacDonald, Heather; Potter, Guy; Burke, James R.
Abstract: Introduction: The Alzheimer's Disease Prevention Registry (ADPR) of the Joseph and Kathleen Bryan Alzheimer's Disease Research Center at Duke University has been successful in achieving a racially diverse and "research ready" cohort of cognitively healthy volunteers. Methods: The ADPR is based on an infrastructure that includes: (1) an administrative leadership team; (2) a coordinating center; (3) an IT management team; (4) a community engagement team; and (5) collaborations with study partners across disciplines. Results: The ADPR currently has more than 4677 members, 26% of whom are African American. The ADPR has supported 21 studies including 8 biomarker studies, 7 clinical trials, 4 cognitive neuroscience studies, and 2 studies assessing novel computerized measures. Discussion: We describe our experiences establishing and maintaining a diverse ADPR as well as insights on recruitment strategies to increase the representation of African Americans in Alzheimer's disease studies.